N6-Methyladenosine Methylomic Landscape of Lung Tissues in Murine Acute Allergic Asthma - Teng, Fangzhou; Tang, Weifeng; Wuniqiemu, Tulake; Qin, Jingjing; Zhou, Yaolong; Huang, Xi; Wang, Shiyuan; Zhu, Xueyi; Tang, Zhao; Yi, La; Wei, Ying; Dong, Jingcheng (Frontiers in Immunology, 2021)
Allergic asthma is well known as a common respiratory disorder comprising the allergic inflammatory nature and excessive immune characteristic. N6-methyladenosine (m6A) methylation, an RNA epigenetic modification that post-transcriptionally regulates gene expression and function by affecting the RNA fate. Currently the m6A methylation is gaining attention as a mechanism of immunoregulation. However, whether m6A methylation engage the pathological process of asthma remains uncertain. Here, we present m6A methylomic landscape in lung tissue of ovalbumin-induced acute asthma mice using MeRIP-seq and RNA-seq. We identify 353 hyper-methylated m6A peaks within 329 mRNAs and 150 hypo-methylated m6A peaks within 143 mRNAs in lung tissues of asthmatic mice. These differentially methylated mRNAs are found to be involved in several immune function-relevant signaling pathways. In addition, we predict 25 RNA-binding proteins that recognize the differential methylated peak sites by exploring public database, and the roles of these proteins are mostly related to mRNA biogenesis and metabolism. To further investigate the expression levels of differentially methylated genes, we perform combined analysis of m6A methylome and transcriptome data, and identify 127 hyper-methylated mRNAs with differential expression (107 high and 20 low expression) and 43 hypo-methylated mRNAs with differential expression (9 high and 34 low expression). Of these, there are a list of mRNAs concerned the immune function and regulation. The present results highlight the essential role of m6A methylation in the pathogenesis of asthma.